Development of Three-Tier Diagnostic Test Instruments to Measure Misconceptions of Class X Students on Atomic Structure Material - Yasmin Nurul Fathonah; Ajat Sudrajat (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: Development of Three-Tier Diagnostic Test Instruments to Measure Misconceptions on Atomic Structure. This study aims to measure misconceptions in atomic structure of tenth grade students at SMA Swasta Nurul Iman Tanjung Morawa. This research was conducted in October 2021-February 2022. The type of research used was Research and Development with the development of ADDIE. Instrument used are tests, questionnaires, interviews and documentation. The diagnostic test developed is a three-tier multiple choice diagnostic test consisting of answer choices, reasons and confidence levels. The results of the validation by the validator show that the instrument developed is valid. The validity of the test developed was 16 valid questions and 4 invalid questions. The results of the reliability test showed a reliability lift of 0.82. The highest percentage of misconceptions is on the concept of electron configuration by 52% and the lowest percentage of misconceptions on the concept of making up atomic particles (protons, electrons, and neutrons) is 21.17%. The percentage of students who understand the concept of atomic structure is 23%. The percentage of categories that do not understand the concept of atomic structure is 32% and the percentage of the category of misconceptions of the concept of atomic structure is 45%.  Keywords: atomic structure, misconception, three-tier multiple choice. DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.14